Global comparison of awake and asleep mapping procedures in glioma surgery: An international multicenter survey. Issue 2 (28th January 2022) - Gerritsen, Jasper K W; Broekman, Marike L D; De Vleeschouwer, Steven; Schucht, Philippe; Jungk, Christine; Krieg, Sandro M; Nahed, Brian V; Berger, Mitchel S; Vincent, Arnaud J P E
Abstract: Background: Mapping techniques are frequently used to preserve neurological function during glioma surgery. There is, however, no consensus regarding the use of many variables of these techniques. Currently, there are almost no objective data available about potential heterogeneity between surgeons and centers. The goal of this survey is therefore to globally identify, evaluate and analyze the local mapping procedures in glioma surgery. Methods: The survey was distributed to members of the neurosurgical societies of the Netherlands (Nederlandse Vereniging voor Neurochirurgie—NVVN), Europe (European Association of Neurosurgical Societies—EANS), and the United States (Congress of Neurological Surgeons—CNS) between December 2020 and January 2021 with questions about awake mapping, asleep mapping, assessment of neurological morbidity, and decision making. Results: Survey responses were obtained from 212 neurosurgeons from 42 countries. Overall, significant differences were observed for equipment and its settings that are used for both awake and asleep mapping, intraoperative assessment of eloquent areas, the use of surgical adjuncts and monitoring, anesthesia management, assessment of neurological morbidity, and perioperative decision making. Academic practices performed awake and asleep mapping procedures more often and employed a clinical neurophysiologist with telemetric monitoring more frequently. European neurosurgeons differed from US neurosurgeons regarding the modality for cortical/subcortical mapping and awake/asleep mapping, the use of surgical adjuncts, and anesthesia management during awake mapping. Discussion: This survey demonstrates the heterogeneity among surgeons and centers with respect to their procedures for awake mapping, asleep mapping, assessing neurological morbidity, and decision making in glioma patients. These data invite further evaluations for key variables that can be optimized and may therefore benefit from consensus.